Exploring the Relationship between population age structure and real exchange rate in OECD countries - Salim, Ruhul; Hassan, Kamrul (World Business Institute Australia, 2012)
This article examines the impact of population age structure on the real exchange rate. Data on a panel of 23 OECD countries over 1980-2009 period are used to estimate the empirical model. The results show that the shares of working age and old dependent population have significant appreciating effects while the share of young dependent has a significant depreciating effect on the real exchange rate. These results have important policy implications given the fact that population is aging in almost all the OECD economies these days.